Potensi Pengembangan Produk Pembiayaan Natural Uncertainty Contract (NUC) Di Bank Syariah Terhadap Sektor Ril UMKM - Trimulato Trimulato (AL-FALAH : Journal of Islamic Economics, 2016)
The data suggests that the financing agreement for the results did not become dominant. The contribution of financing in sharia’ah banks with murabahah sale and purchase agreement of 63.868 percent. Islamic economics can not be separated from the real sector, especially SMEs, its existence requires the support of other parties, including shari’ah banks. Financing products with mudharabah it is appropriate to sustain the business capital of SMEs. Based on data that the growth of SMEs in 2013 of 56,534,591 into 57,895,721 or grow around 2.408 percent. It takes a good response for shari’ah banks to provide financing for SMEs. This paper uses a descriptive qualitative. The paper is focused on products with the financing agreement Uncertanty Natural Contract (NUC) at the shari’ah bank and real sector SMEs. The research uses literature study from various sources. The results descrobes that the potential development of financing products with NUC contract in shari’ah bank is still very large. It is seen that the number of SMEs continues to grow, then the portion of financing products are still small. This indicates that the loan product NUC financing in shari’ah banks are very suited to the conditions and character of SMEs. Potential financing agreement NUC product development in Islamic banks are still very large and very spacious. Keywords : Potential, Shari’ah Banking, Natural Uncertanty Contract (NUC),Real Sector and SMEs.